Staff governance and institutional policy formation - Miller, Michael T.; Murry, John W. (Educational policy in the 21st century., 2011)
The number of staff members serving American higher education institutions has more than doubled in the past twenty years, as occupations in technology, development, government relations, and even athletic administration have grown as never before in the history of the academy. As the number, variety, and importance of these positions have grown, so has the need for their involvement in determining the direction and vision of the contemporary university. Often in opposition or cast in a competing light, staff governance bodies are positioned within the governance framework of faculty, students, trustees, and even legislatures, all bound together by formal and legal authority guidelines. The current volume is among the very first to explore this landscape, and begins with a critical evaluation of the context of how staff are involved in decision-making. The text devotes six chapters to an in-depth exploration of the environment where staff governance is used: in private and community colleges, with athletics and student affairs, in collective bargaining environments, and how the inclusion of staff can be an asset to institutional self-determination. The final section describes the array of topics staff governance bodies address, and shares a case study of one professional administrator who chaired a staff senate. The concluding chapter outlines the implications in policy formation, evaluation, and agenda setting for the involvement of staff in the higher education community. The book is a must read for new, senior college administrators, staff governance leaders, practitioners in human resource management, those concerned about democracy in education, and scholars studying higher education management.